A methodology for trust and risk mash up for enhanced business intelligence in cloud environment - Hammadi, Adil Mumtaz (Curtin University, 2014)
With the advancement of cloud computing, enterprises are moving their IT infrastructure to clouds. However, in adopting cloud services, Quality of Service (QoS) concerns need to be addressed for SLA management. In this thesis, an SLA management framework from a consumer’s point of view is proposed that first selects a trustworthy service provider who is capable of providing the requested service; and then monitors the performance of service delivery to ensure the quality of service.